Infection-induced inflammatory response of adipocytes in vitro - Bouwman, J.J.M; Visseren, F.L.J; Bouter, K.P; Diepersloot, R.J.A (International Journal of Obesity, 2008)
Background: Abdominal obesity plays an important role in the development of insulin resistance, diabetes mellitus and atherosclerosis. The exact pathophysiological mechanisms are unclear but adipocyte dysfunction is thought to be crucial. Infections are associated with the development of atherosclerosis as well as diabetes. In this study we investigated whether adipocytes can be infected and whether this results in production of inflammatory cytokines relevant for the development of atherosclerosis and diabetes. Methods: Pre-adipocytes were cultured and differentiated into mature adipocytes in vitro. Adipocytes and pre-adipocytes were incubated with infective and heat-inactivated Chlamydia pneumoniae, cytomegalovirus (CMV), adenovirus (Ad) subtypes 2 and 36, influenza A and respiratory syncitial virus (RSV). After 48 h, adiponectin, interleukin-6 (IL-6), tumor necrosis factor- (TNF-) and plasminogen activator inhibitor-1 (PAI-1) were measured in supernatants. Results: Infection of adipocytes with Ad-36, CMV and RSV resulted in increased IL-6 production from 19222 pg ml- 1 (uninfected) to 103086 pg ml- 1, 83859 pg ml- 1 and 1241191 pg ml- 1, respectively (all P<0.01 vs control). In addition, Ad-36 infection slightly reduced PAI production in adipocytes (28526.8 ng ml- 1 vs uninfected: 47771.2 ng ml- 1; P=0.05) and pre-adipocytes (70943.3 ng ml- 1 vs uninfected: 107171.8 ng ml- 1; P<0.01). In contrast, human Ad type 2 did not exert any effect on IL-6 or PAI production. None of the microorganisms induced significant changes in adiponectin and/or TNF- production. Conclusions: Adipocytes can be infected with several microorganisms in vitro. Infection of adipocytes with Ad-36, but not Ad-2 leads to increased production of IL-6 which might contribute to chronic low-grade inflammation, a process known to be involved in the development of cardiovascular diseases and type 2 diabetes.